2007
DOI: 10.1007/bf02940310
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate notch activity and limited mesenchymal stem cell plasticity in the bone marrow of patients with myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDSs) are a heterogeneous group of hematological disorders characterized by ineffective hematopoiesis, enhanced bone marrow apoptosis and frequent progression to acute myeloid leukemia. Several recent studies suggested that, besides the abnormal development of stem cells, microenvironmental alterations are also present in the MDS bone marrow. In this study, we have examined the relative frequencies of stem and progenitor cell subsets of MDS and normal hematopoietic cells growing on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 31 publications
4
50
1
1
Order By: Relevance
“…These observations agree with the findings of several previously published studies, 7,10,12,29,30 but contrast with the data from others 6,9,13 in which MDS-MSC had normal growth. The contradiction might be attributed to the heterogeneity of MDS patients.…”
Section: Discussionsupporting
confidence: 91%
“…These observations agree with the findings of several previously published studies, 7,10,12,29,30 but contrast with the data from others 6,9,13 in which MDS-MSC had normal growth. The contradiction might be attributed to the heterogeneity of MDS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Mellibovsky et al showed that MDS patients have a typical adynamic bone with decreased mineral deposition 31 and a recent study by Raaijmakers demonstrated how Dicer1 deletion in mice osteoprogenitors leads to bone dysfunction and development of MDS that progresses to AML. 10 Varga et al 25 previously described similar defective adipogenic differentiation in MDS-MSC. Defects of differentiation potential of MSC might have a role in MDS pathophysiology.…”
Section: Discussionmentioning
confidence: 80%
“…20,23,32,33 Varga et al showed that MDS-MSC provide reduced hematopoietic support. 25 Regarding the influence of MSC on CD34 + cell differentiation, we provide the first evidence of a specific deficiency of MDS-MSC correlating with disease category. It remains to be investigated which pathways are involved in the dysregulated induction of differentiation.…”
mentioning
confidence: 68%
See 2 more Smart Citations